Peroperační verifikace integrity kolorektální anastomózy - Martínek, L; Bergamaschi, R; Hoch, J (Rozhledy v chirurgii, 2015)
Early postoperative anastomotic complications have serious clinical implications for the patients morbidity, mortality as well as long-term results. A number of measures can be undertaken to reduce the risk of anastomotic complications, including intraoperative colorectal anastomotic integrity assessment. Methods used to assess anastomotic reliability have gradually developed from basic mechanical techniques, direct visual endoluminal inspection, to microperfusion assessment of perianastomotic tissue. Moderate benefit in terms of reduced postoperative anastomotic complications has been shown with mechanical patency testing and partly with intraoperative endoscopic visualization of colorectal anastomoses. More recently, indocyanine green (ICG) fluorescence imaging methods have emerged as major contributions to anastomotic patency assessment and intraoperative decision making during surgical colorectal procedures including decreased numbers of ileostomies.
Keywords: Anastomosis, Surgical; Coloring Agents; netěsnost anastomózy; Reproducibility of Results; Anastomotic Leak; anastomóza chirurgická; kolon; peroperační monitorování; Indocyanine Green; Humans; lidé; Monitoring, Intraoperative; Rectum; rektum; barvicí látky; Colon; reprodukovatelnost výsledků; indokyanová zeleň